Roads investment and economic growth : similarity or divergence between developed and developing countries : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Planning at Massey University, Manawatū, New Zealand - Chohan, Muhammad Babar (Massey University, 2016)
This research investigates how arguments for economic growth are perceived and advanced to promote road investment. In particular, it addresses the question of whether there is similarity or divergence between developed and developing countries given their different growth trajectories. In literature, the relationship between building roads and achieving economic growth is heavily reliant on quantitative tools while ignoring the socio-economic and political contextual details of developed and developing countries. Using the Aristotelian concept of phronēsis, the research undertakes a comparative case study involving New Zealand and Pakistan. Phronēsis is an intellectual virtue capable of incorporating practical problems and contextual issues in everyday life. The concept was operationalized for this thesis by devolving it into three main questions in which the roads policy direction, the associated processes and discursive pragmatism was explored. Detailed analysis of two major roading infrastructure projects, MacKays to Peka Peka (M2PP) in the Wellington region of New Zealand and a Ring Road in Lahore, Pakistan, shows that roads investment is promoted on the basis of national visions and policies without robust evidence of how economic growth will be achieved. The findings indicate that the national visions, related to case study projects, are not based on robust analyses and research but rather on strategic needs that advance the agenda of the powerful. The research found that the discourse of economic growth in each project was based on similar arguments about travel time saving, efficiency and employment growth regardless of public consultations. The research concludes that ‘economic growth’ is a niche created, advanced, and interpreted by power to achieve its strategic objectives in road development without contextual differences being considered in developed and developing countries.
Keywords: Roads; Economic aspects; Pakistan; Lahore; New Zealand; Wellington Region; Phronesis; Developing countries